Novel ReBaCo1.5Mn0.5O5+δ (Re: La, Pr, Nd, Sm, Gd and Y) perovskite oxide: influence of manganese doping on the crystal structure, oxygen nonstoichiometry, thermal expansion, transport properties, and application as a cathode material in solid oxide fuel cells. Issue 27 (21st June 2018) - Olszewska, Anna; Du, Zhihong; Świerczek, Konrad; Zhao, Hailei; Dabrowski, Bogdan
Abstract : Introduction of Mn, on the order of 0.5 in ReBaCo1.5 Mn0.5 O5+ δ, allows to develop a very good cathode material for SOFCs, as shown for Re = Nd. Abstract : In this work, a novel series of Mn-containing ReBaCo1.5 Mn0.5 O5+ δ (Re: selected rare earth elements) perovskite-type oxides is studied, with systematic measurements of physicochemical properties being reported. Comparison with the very well-studied, parent ReBaCo2 O5+ δ allows determination of the role of the introduced manganese concerning modification of the crystal structure at room temperature and its evolution at high temperatures, variation of the oxygen content, thermal stability of the materials, and total electrical conductivity, as well as thermal and chemical expansion. Generally, the presence of Mn cations does not affect the tendency for A-site cation ordering, resulting in an increased unit cell volume of the compounds, as well as causing an increase of the oxygen content. Reduced thermal expansion, together with high values of electrical conductivity and suitable thermal stability, makes the compounds containing larger Re 3+ cations attractive from the point of view of application as cathode materials in solid oxide fuel cells. Chemical compatibility studies reveal the sufficient stability of the considered perovskites in relation to Ce0.8 Gd0.2 O2− δ solid electrolyte, while unexpected, somewhat increased reactivity towards La0.8 Sr0.2 Ga0.8 Mg0.2 O3− δ and La0.4 Ce0.6 O2− δ is also reported. Furthermore, the electrochemical tests of the symmetric cells show strong dependence of the polarization resistance of the electrode on the synthesis and sintering temperatures. For the selected and optimized NdBaCo1.5 Mn0.5 O5+ δ layer employed in the electrolyte-supported (LSGM) symmetric cell with a CGO buffer layer, the cathodic polarization resistance is 0.043 Ω cm 2 at 900 °C. A wet hydrogen-fuelled button-type cell with the NdBaCo1.5 Mn0.5 O5+ δ -based cathode is also prepared, delivering the maximum power density exceeding 1.3 W cm −2 at 850 °C.